GENETIC DIVERSITY AND PRODUCTIVE PERFORMANCE IN LOCAL AND IMPORTED IRAQI COWS USING MICROSATELLITE MARKERS - S. M. Al-Jub; Riyadh Hamad senkal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The study was conducted us to identify the genetic features of the microsatellite markers CSSM66 and ETH10 and ILSTS34 and their relationship to genetic diversity and productive performance this study was carried out using 100 cows of five breeds presented in Iraq ; Restaki (n=10) , Janoubi (n=10) , Sharabi (n=10) , (local), Holstein (n=50) and male Brahman (n=20) (imported).The results showed the presence of a very high diversity and a highly significant difference in a sample of studied cows in the allele distribution ratios for the three markers, the results showed a significant effect (P≤0.05) superiority of the genotype LY within the ETH10 marker in the least number of inseminatons required for fertilization of Restaki cows, namely 1.16 insemination, and the genotype GP and AB within ETH10 and CSSM66 markers, respectively, recorded the highest total average milk yield with a significant value (P≤0.05) for Holstein cows, reached 1.44 . The CC genotype within markers CSSM66 had the highest mean total weight with an average of 502.75 among Brahman bulls. Therefore, microsatellites markers contributed to the mapping of quantitative traits in the studied cows